1998
DOI: 10.1111/j.1475-4754.1998.tb00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Quartz‐tempered Ceramics: Part I, Strength and Toughness*

Abstract: The effect of quartz temper on the physical and mechanical properties of clay ceramics and the elucidation of the underlying mechanisms that are responsible for these efsects are presented here. Characteristics studied included bulk density, open and closed porosity, density of impervious portion and fracture morphology. Mechanical behaviour was studied by measuring energy dissipation during fracture, Young's modulus, initial fracture toughness and strength in flexure. The signifcant increase in toughness with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 22 publications
5
91
1
2
Order By: Relevance
“…It is apparent then that temper affects drastically the performance characteristics of the fired ceramic bodies, something which attracted substantial attention in the last three decades. The studies have mainly reference to archaeological pottery, trying to explain changes of tempering traditions with time and use (Steponatis, 1984;Sabrah and Ebied, 1985;Bronitsky and Hamer, 1986;Okongwu, 1988;Hoard et al, 1995;Kilikoglou et al, 1995Kilikoglou et al, , 1998Hein et al, 2008;Garcia-Ten et al, 2010a,b;Hein et al, 2013;Allegretta et al, 2014).…”
Section: -850åcmentioning
confidence: 98%
“…It is apparent then that temper affects drastically the performance characteristics of the fired ceramic bodies, something which attracted substantial attention in the last three decades. The studies have mainly reference to archaeological pottery, trying to explain changes of tempering traditions with time and use (Steponatis, 1984;Sabrah and Ebied, 1985;Bronitsky and Hamer, 1986;Okongwu, 1988;Hoard et al, 1995;Kilikoglou et al, 1995Kilikoglou et al, , 1998Hein et al, 2008;Garcia-Ten et al, 2010a,b;Hein et al, 2013;Allegretta et al, 2014).…”
Section: -850åcmentioning
confidence: 98%
“…The low firing temperature in the kiln used to produce the "Losanga" pottery under investigation is further confirmed by the absence of bright reaction rims formed by Ca-rich silicate phases (such as diopside, gehlenite and anorthitic plagioclases) which typically form in Ca-rich ceramics when fired at higher temperatures [2]. In terms of microfabric porosity in the temper, fissures at quartz grain boundaries as a result of shrinkage of clay minerals during drying and expansion of quartz crystals from α to β phases during firing [10,34] are present, particularly in samples from Andalucia where secondary porosity typically with rounded pores can also be seen. Illitic laths while maintaining their sheet-like typical habit, show separation along basal cleavage planes (Fig.…”
Section: Ceramic Bodymentioning
confidence: 81%
“…According to a previous research [13] the hysteresis observed in porcelain materials is attributed to microcracking on cooling and healing of the microcracks during heating, in the region around the - quartz transition. Moreover, as set out elsewhere [17][18], porosity and metakaolinite transformation in the 429-740°C temperature range, in the early firing stage, negatively affect the Young's modulus behavior. On the other hand, as reported [4] cristobalite formation on cooling in the 225-250°C temperature range and residual mullite may act as a microstructural reinforcing and so improving the mechanical strength of quartz porcelains.…”
Section: Introductionmentioning
confidence: 89%